Personality traits and emotional intelligence in internal drug dependent patients in two rehabilitation centers of Lima East - Zela Bravo, Raúl Stifp (2019)
Objective: To determine the relationship between personality traits and emotional intelligence in drug-dependent patients, from 14 to 18 years old, inmates in two rehabilitation centers in Lima East. Methodology: The type of study is quantitative, correlational in scope and cross-sectional. The sample consisted of 153 participants. The model of the personality traits on which we work is the model of the big five of Costa and McCrae (1992). The scale to measure personality traits was the NEO FFI Personality Inventory (abbreviated version), whose Peruvian adaptation was carried out by Martínez and Cassaretto (2005). To measure emotional intelligence levels, we used the Emotional Intelligence Inventory ICE BARON (abbreviated version), prepared by Baron (1997) and adapted by Ugarriza and Pajares (2011). Results: It was evidenced that there is no significant relationship between both study variables. In addition, no significant relationship was found between emotional intelligence with the dimensions of extroversion, neuroticism, openness to experience, kindness and responsibility.Conclusion: there are other factors that intervene in the relationship of personality traits with the emotional intelligence of the participants.